Edukasi Tips Memilih, Mengolah, dan Menyajikan Makanan yang Aman pada Mahasiswa STIKES Graha Medika Secara Daring Menggunakan Aplikasi Zoom Cloud Meetings - Hairil Akbar; Sarman; Muhammad Ichsan Hadiansyah (Jurnal Pengabdian UntukMu NegeRI, 2021)
Efforts to achieve Indonesian citizen with quality are closely related to food and nutrition factors. Fulfillment of food and nutrition adequacy can be seen from the level of food provided and the quality and diversity of food and nutrition available. Approximately 70% of cases of food poisoning in the world are caused by ready-to-eat food, namely processed food, especially by catering businesses, restaurants, canteens, restaurants, or street food. Food poisoning is usually caused by the food being contaminated with bacteria or microbes. The purpose of this community service is to increase students' knowledge and understanding regarding selecting, processing, and serving safe food. Methods used consisted of counseling and health education on tips for selecting, processing, and serving food using the zoom cloud meeting application, with the target of Graha Medika Kotamobagu Health Institute students. The activity was held on Monday, October 12, 2020. The results of the community service activities showed that of the 34 students who participated in the activity, 80% of students knew and could mention tips on choosing, processing, and serving safe food. The implementation of social service is very important to increase knowledge in selecting, processing and serving food that is safe for consumption.